PECULIARITIES OF THE FINANCIAL MECHANISM OF ENVIRONMENTAL MANAGEMENT (Economic journal of Lesya Ukrainka Volyn National University, 2024)
Humans inherently interact with nature in all areas of their lives. Today, there is a significant anthropogenic impact on the environment. On the one hand, there is research and protection of nature, and on the other hand, consumption and transformation. Many processes begin with the use of natural resources and end with emissions. Therefore, the key task of society is to minimize negative changes in the environment. The financial mechanism can be considered one of the most effective alternatives in achieving environmental goals, and its construction and efficiency directly depend on the specifics of the area in which it operates. The purpose of the study is to determine the peculiarities of building a financial mechanism for environmental management. In the course of the work, the author analyzes the works of domestic and foreign scholars who deal with the issues of the financial mechanism of environmental management. Using such general scientific methods as analysis, synthesis, systematization, and generalization, the author assesses the financial mechanism of natural resource management and identifies the key features of natural resource management that serve as the basis for the mechanism under study. It is determined that relations in the field of the financial mechanism of environmental management should be considered through transaction costs arising in relations where each party seeks to obtain a certain benefit with the simultaneous existence of a potential conflict of interest. The formation of environmental protection policy, and the financial mechanism of environmental management in particular, is influenced by state institutions, business entities, and individuals who consume resources and generate emissions. Among the features of natural resource management that affect the financial mechanism are the following: socio-ecological balance, public participation, environmental sustainability, legislative regulation, environmental impact assessment, and conservation of natural resources. It is established that in order to ensure rational use of natural resources, it is necessary to carry out effective planning and management; and to form regulators of influence and stimulating factors.
Keywords: environmental management; financial mechanism; features, financial policy; environment; transaction costs.